The Lexus and the olive tree - Friedman, Thomas L. (New York Farrar, Straus, 2000)
In The Lexus and the Olive Tree, Friedman offers an engrossing look at the new international system that is transforming world affairs today. Globalization has replaced the Cold War system with the integration of capital, technology, and information across national borders.
Includes index.
Keywords: International economic relations